Penatalaksanaan Hiperkolesterolemia Dan Obesitas Grade II Pada Pasien Wanita Usia 47 Tahun Melalui Pendekatan Kedokteran Keluarga - Ebti Rizki Utami; Reni Zuraida (CV. Jasa Sukses Abadi, 2020)
The prevalence of hypercholesterolemia in Indonesia at the age of 25-34 years is 9.3% and increases with age up to 15.5% at the age of 55-64 years. Hypercholesterolemia is generally found in women (14.5%) than men (8.6%). This case report aims to identify risk factors and patient clinical problems to improve the patient's quality of life and carry out holistic and comprehensive management based on Evident Based Medicine which is family-approach and patient-centered. Primary data were obtained through anamnesis, physical examination and home visits. Secondary data were obtained from patient medical records. The assessment was carried out based on a qualitative and quantitative initial to final holistic diagnosis so that data were obtained in the form of a female patient aged 47 years, diagnosed with hypercholesterolemia and grade II obesity. Limited knowledge regarding the prevention of hypercholesterolemia and grade II obesity, foods that need to be avoided and the lack of motivation and family encouragement to bring patients to control their health regularly are factors that cause problems that occur in patients. Management in the form of simvastatin 1x10 mg and counseling about the patient's health condition. Then the evaluation was carried out by checking total cholesterol, the results of the pre-test 40 and the post-t test 80. There was an increase in the knowledge score including how to calculate ideal body weight, normal total cholesterol value in the body, normal value of BMI, and factors that cause increased cholesterol in the body. Management with a family medicine approach is proven to increase patient knowledge about their health condition and change their life behavior.